The global NAFLD policy review and preparedness index: Are countries ready to address this silent public health challenge? - Lazarus, Jeffrey V; Mark, Henry E; Villota-Rivas, Marcela; Palayew, Adam; Carrieri, Patrizia; Colombo, Massimo; Ekstedt, Mattias; Esmat, Gamal; George, Jacob; Marchesini, Giulio; Novak, Katja; Ocama, Ponsiano; et al. (Elsevier BV, 2022)
Non-alcoholic fatty liver disease (NAFLD) is a highly prevalent, yet largely underappreciated liver condition which is closely associated with obesity and metabolic disease. Despite affecting an estimated 1 in 4 adults globally, NAFLD is largely absent on national and global health agendas.
Keywords: non-alcoholic fatty liver disease (NAFLD); non-alcoholic steatohepatitis (NASH); liver health; global public health; policy preparedness; health policy; multiple correspondence analysis